Unbiased molecular dynamics simulation of a first-in-class small molecule inhibitor binds to oncostatin M. (March 2023) - Du, Qingqing; Tu, Gao; Qian, Yan; Yang, Jingyi; Yao, Xiaojun; Xue, Weiwei
Abstract: Small molecule inhibitors (SMIs) targeting oncostatin M (OSM) signaling pathway represent new therapeutics to combat cancer, inflammatory bowel disease (IBD) and CNS disease. Recently, the first-in-class SMI named SMI-10B that target OSM and block its interaction with receptor (OSMR) were reported. However, the binding pocket and interaction mode of the compound on OSM remain poorly understood, which hampering the rational design of SMIs that target OSM. Here, using SMI-10B as a probe, the multiple pockets on OSM for small molecules binding were extensively explored by unbiased molecular dynamics (MD) simulations. Then, the near-native structure of the complex was identified by molecular mechanics generalized Born surface area (MM/GBSA) binding energy funnel. Moreover, the binding stabilities of the protein-ligand complexes in near- and non-native conformations were verified by additional independent MD runs and absolute free energy perturbation (FEP) calculation. In summary, the unique feature of SMI-10B spontaneously binds to OSM characterized here not only provide detailed information for understanding the molecular mechanism of SMI-10B binding to OSM, but also will facilitate the rational design of novel and more potent SMIs to block OSM signaling. Graphical abstract: Image 1 Highlights: Multiple binding pockets on OSM for SMIs were extensively explored by unbiased MD simulations. The near-native structure of the first-in-class inhibitor SMI-10B in complex with OSM was identified. The mechanism underlying the binding of SMI-10B to OSM will facilitate the rational design of novel and more potent SMIs targeting OSM.